PENGARUH KOMPETENSI, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU SMAS ST. FAMILIA WAE NAKENG MANGGARAI BARAT NTT - Angela Kurniati Kunda; Supriyoko; Rejokirono (STKIP Subang, 2023)
This study aims to determine the influence of Competence, Work Motivation and Work Environment on Teacher Performance at SMAS St. Familia Wae Nakeng Manggarai Barat NTT and determine the effect of Competence, Work Motivation, Work Environment individually on Teacher Performance at SMAS St. Familia Wae Nakeng West Manggarai NTT. This research was conducted at SMAS St. Familia Wae Nakeng West Manggarai NTT. The research time is from November 2022 to February 2023. This research uses a quantitative approach. The population of this research is SMAS St. teacher. Familia Wae Nakeng Manggarai Barat NTT, totaling 65 teachers. In this study, researchers used a saturated sampling technique, which is a sampling technique if all members of the population are used as samples. By taking a sample of 65 teachers. Collecting data using a questionnaire technique, previously tested the validity and reliability. Data analysis using descriptive analysis, analysis prerequisite testing. Hypothesis testing using the product moment technique and linear regression. The results of this study indicate that competence, work motivation, and work environment together have a positive and significant influence on the performance of SMAS St. Familia Waenakeng Manggarai Barat NTT teachers' performance, this shows that the better the competence, the higher the motivation to work, and the better the work environment has a better influence on teacher performance. Competence, work motivation, and work environment individually have a positive and significant influence on the performance of St. SMAS teachers. Familia Waenakeng Manggarai Barat NTT, this shows that increasing competency, work motivation, and work environment individually will increase teacher performance, conversely decreasing competence, work motivation, and work environment individually will reduce teacher performance.